Designing Climate Information Services to Enhance Resilient Farming Activities: Lessons From Papua New Guinea - Friedman, Rachel S.; Mackenzie, Ellis; Baiga, Ruth; Inape, Kasis; Crimp, Steven J.; Howden, Mark (Frontiers in Climate, 2022)
Anthropogenically-driven changes in seasonal climate patterns are already jeopardising traditional farming practices all around the world. These climatic changes increasingly expose farmers to challenging conditions, reducing the efficacy of existing farm practices and productivity. There is a plethora of information, tools, and practices that could be useful for farmers trying to respond to climate variability and change, including climate projections, horticultural advances, and agricultural management best practices. Whilst these tools and knowledge exist, they are often not contextualised in ways that equitably facilitate decision-making and action. To ensure weather and climate information services are accessible and useful to farmers, it is critical to understand and integrate considerations for the desired types, timing, and uses of the information. The one-size-fits-all information services that are often available don’t account for regional or social differences, local physical conditions, or the needs of different populations. In order to improve our understanding of how weather and climate information services can better cater to farmers’ needs when modifying and adapting their goals, risk management, and farm practices, we carried out a household survey in communities across three provinces in Papua New Guinea. The survey was developed to draw out key design considerations for seasonal climate forecasts in terms of timing, type of information, and applications. Based on the clustering and associations of these variables, his study identifies different profiles of information services content. It then examines whether specific profiles are associated with demographic groups or geographic locations. The findings demonstrate gender and geographic differences in the desired bundles of weather and climate information, and therefore can help to pinpoint specific components that would be beneficial to incorporate into extension and outreach programmes in different contexts within Papua New Guinea. This study highlights the value of tailoring weather and climate information services with specific groups of farmers, thereby enabling more equitable access to and use of critical knowledge for smallholders to build the capacity, knowledge, and systems to strategically adapt to climate change. At the same time, this study illustrates areas to gain efficiency and potentially scale up the provision of climate information services.